Genetic diversity, essential oil’s chemical constituents of aromatic plant Mesosphaerum suaveolens (L.) Kuntze Syn. Hyptis suaveolens (L.) Poit. and its uses in crop protection: a review - Dossa, Armel Frida; Fassinou Hotegni, Nicodème V.; N’Danikou, Sognigbé; Yayi-Ladekan, Eléonore; Adjé, Charlotte A. O.; Lagnika, Latifou; Bokonon-Ganta, Aimé H.; Achigan-Dako, Enoch G. (Frontiers in Plant Science, 2024)
This review provides evidence on the genetic diversity, chemical constituents, and ecotoxicology of Mesosphaerum suaveolens ’ essential oil. It emphasizes the agricultural benefits such as crop protection effectiveness of the plant and highlights the existing knowledge gaps and research perspectives to promote its utilization in agriculture. A systematic and extensive review of the literature was done and all pertinent full-text articles and abstracts were analyzed and incorporated into the review. Mesosphaerum suaveolens is used traditionally in pharmacology to treat several diseases such as malaria, constipation, stomach problems, and renal inflammation. It also treats cramps, digestive infections, headaches, and skin infections. To date, very few studies have been conducted worldwide about its genetic diversity. These studies highlighted three morphological variants, the blue-flowering, the white-flowering, and the light-purple flowering M. suaveolens . Its wide biological actions may be attributed to the numerous groups of chemical constituents in its essential oil including monoterpenes, sesquiterpenes, and diterpenes. Biological studies highlighted evidence of M. suaveolens being used as an antifungal, bactericidal, antimicrobial, insecticidal, and repellent plant. The essential oil extracted from M. suaveolens showed significant potential for the control of agricultural pests such as Sitiophilus zeamais, Helicoverpa armigera and Helminthosporium oryzae. M. suaveolens is commonly used worldwide as a pesticidal plant in healthcare, agriculture, and food preservation. However, there is a lack of studies concerning the toxicity and effectiveness of isolated potent phytotoxic substances, the efficacy screening in the field, the genetic diversity, the essential oil yield, and productivity. Consequently, further studies are required to fill the knowledge gaps.